2013
DOI: 10.1103/physrevb.87.060409
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced ferromagnetism in antiferromagnetic Fe1.03Te

Abstract: The magnetic properties of Fe1.03Te under hydrostatic pressure up to p 5.7 GPa were investigated by means of muon spin rotation, dc magnetization, and neutron depolarization measurements. With increasing pressure the antiferromagnetic ordering temperature TN decreases continuously from 70 K at ambient pressure towards higher pressures. Surprisingly, the commensurate antiferromagnetic order of FeTe enters a region of incommensurate and dynamical magnetic order before at p 1.7 GPa the system turns ferromagnetic.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 34 publications
9
43
1
Order By: Relevance
“…This is in reasonable agreement with results of Ref. [40], where the ferromagnetic state was observed in FeTe for the first time under pressures of P ≥ 20 kbar.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in reasonable agreement with results of Ref. [40], where the ferromagnetic state was observed in FeTe for the first time under pressures of P ≥ 20 kbar.…”
Section: Discussionsupporting
confidence: 82%
“…As appears from the present calculations of the pressure effect on χ for FeSe 0.5 Te 0.5 and the earlier similar calculations for FeSe and FeTe, the large positive pressure effect on susceptibility in FeSe 1−x Te x compounds is determined by the dominating positive contribution caused by the strong sensitivity of paramagnetic susceptibility to internal structural parameter Z and its change under pressure. It should be noted that the largest pressure effect on χ appears in FeTe compound, and that is a source of the observed its ferromagnetic state at high pressures [40].…”
Section: Discussionmentioning
confidence: 99%
“…Ferromagnetic order is much less usual than antiferromagnetism in Fe superconductors but it has been observed in a few cases [15-19, 23, 24, 269, 270]. [(Li 1−x Fe x )OH]FeSe based [15][16][17][18][19] [23,24]. This variety of magnetic patterns indicates the magnetic order in these systems is soft, namely, it can be affected by small changes in parameters.…”
Section: Magnetic Softnessmentioning
confidence: 99%
“…The measured magnetic moment of Fe in Fe 1+x Te is about 2.25 B µ [103], larger than those of Fe-As compounds. Recently it is found that Fe 1.03 Te becomes ferromagnetic with application of pressure and the magnetic moment per Fe atom reaches about 3 B µ at the highest pressure investigated [105]. Fe 1+x Se is nonmagnetic and shows tetragonal to orthorhombic structure transition at 90 K [106].…”
Section: Structurementioning
confidence: 99%